eNaTIS : what went wrong? - Townsend, Stephanie; Whittaker, Louise ([London] : SAGE, 2016)
On 31 May 2007, Werner Koekemoer, project manager for the eNaTIS (a new national traffic information system) in the Department of Transport (DoT), and Johan Vorster, project director of Tasima (the consortium that had developed the system), met to reflect on the highly publicised failure of the new traffic information system on 12 April, just over a month before. Jeff Osborne, chief executive of the Retail Motor Industry Organisation, had been particularly scathing. "Matters are in a state of chaos," he had said. "The failure to register new and pre-owned vehicles has affected everybody's cash flow. We have lost a billion rands and thousands of deals. The system is worse than the old one." It had been a very stressful time.
Originally Published in: Townsend, S. & Whittaker, L. (2008). eNaTIS: What Went Wrong? WBS-2008-7. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Intelligent transportation systems -- South Africa -- Case studies; Project management -- Case studies